Molecular Dissection of Constans (CO) Homologs and Their Regulatory Role in Floral Induction of Mango (Mangifera indica L.) - Muthukumar, M.; Bajpai, Anju; Khan, Kasim; Bajpai, Yashi; Kumar, Sandeep; Soni, Sumit Kumar; Laxmi; Singh, V. K.; Damodaran, T. (Applied Fruit Science, 2025)
Constans (CO), one of the key transcription factors of the zinc finger family, plays a crucial role in the photoperiodism-dependant flowering pathway. A systematic structural and functional analysis of the CO gene homologs need to be conducted in mango cultivars with contrasting bearing behaviors: ‘Amrapali’ (regular) and ‘Chausa’ (irregular). RNA-Seq leaf transcriptomes were mined for CO homologs and predicted structural variations using bioinformatics and validated by real time polymerase chain reaction (PCR) analysis. Seven CO homolog classes were identified. A partial CO gene sequence of ‘Amrapali’ generated by Sanger sequencing was identified as CO5 homolog. Phylogenetic analysis clustered these homologs into four clades comprising CO2, CO5, and CO16 in three distinct clades and 4th clade harboring other CO homologs. Genomic location of CO2 and CO16 homologs were mapped on chromosomes 15 and 4, respectively, in the mango genome, while CO5 homologs were located on chromosomes 13 and 17. CO2 and CO5 homologs were categorized as a group‑I class with two zinc finger B‑boxes near N‑terminus, while CO16 homologs belong to the group-III with one B‑box and a diverged zinc finger. CO homologs showed structural variations in transcripts and proteins contributing to their multi-functional roles. Gene expression analysis proved that even new shoots of ‘Amrapali’ (010) showed significantly higher upregulation of CO expression on par with that recorded in the leaves from the old shoots of ‘Chausa’ (319). Group I class of homologs is a critical factor determining floral induction in mango
Publisher Copyright: © The author(s), exclusively licensed to Springer-Verlag GmbH Germany, a part of Springer Nature 2025.
Keywords: CO transcription factor; Flowering; Mango transcriptome; Photoperiodism; qRT-PCR